Exploration of synthetic lethal interactions as cancer drug targets - Kuiken, Hendrik J; Beijersbergen, Roderick L (Future oncology (London, England), 2010)
In cancer research the quest continues to identify the Achilles heel of cancer. The ideal cancer drug targets are those that are essential in tumor cells but not in normal cells. Such targets are defined as cancer-specific vulnerabilities or as synthetic lethal interactions with cancer-specific genetic lesions. The search for synthetic lethal interactions focuses on proteins that are frequently mutated but elude pharmacological inhibition, for example, RAS, or proteins that are lost in cancer cells and by definition cannot be targeted, such as the tumor suppressor genes , and . These genetic interactions could yield alternative, effective targets for cancer treatment. However, it remains very difficult to predict or extrapolate these synthetic lethal interactions based on existing knowledge. With the discovery of RNAi, unbiased large-scale functional genomic screens for the identification of such targets have become possible potentially leading to major advances in the treatment of cancers. In this review we will discuss the biological basis of synthetic lethal interactions in relation to existing targeted therapeutics, lessons taught by targeted therapeutics already used in the clinic and the implementation of RNAi as tool to identify such synthetic lethal interactions.